Scimitar syndrome - Özme, Şencan; Tuncalı, Tahsin; Saraçlar, Muhsin (The Turkish Journal of Pediatrics, 1970)
A case of Scimitar Syndrome in a child is presented and the features of the syndrome were discussed. The main pathology of the syndrome is the anomalous drainage of all or some of the right pulmonary veins into the inferior vena cava below the diaphragm. These veins form a characteristic scimitar-shaped shadow along the right atrial silhouette on frontal roentgenograms. In the pediatric age group, it is more common in females. The prognosis of the individuals with this malformation is related to the severity of the pulmonary hypoplasia and associated cardiac malformations.